Gulo gulo subsp. luscus Linnaeus 1758 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Gulo gulo subsp. luscus Linnaeus 1758 Synonyms: Gulo gulo subsp. auduboni Matschie 1918; Gulo gulo subsp. bairdi Matschie 1918; Gulo gulo subsp. hylaeus Elliot 1905; Gulo gulo subsp. luscus Sabine 1823; Gulo gulo subsp. niediecki Matschie 1918. Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Carnivora, pp. 532-628 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 607, DOI: 10.5281/zenodo.7316519